Dependence of the blood supply area sizes of the adrenal glands from characteristics of the arterial blood source - E. V. Timofeeva; S. V. Lopatina (Acta Biomedica Scientifica, 2018)
The current article describes the determined blood supply areas of each of the suprarenal arteries. It is stated, that the intraorganic arteries branch out in the capsule and cortex mainly dichotomically, while in the brain matter the arteries are distributed according to the evriareal type of the vascular tree. The superior suprarenal arteries supply blood to the upper pole of the adrenal gland, to its anterior and posterior surfaces till the level of the horizontal fissure. The area of the blood supply ranges from 1.95 х 103 to 4.12 х 103 mm2, the degree of involvement 34 %. The middle suprarenal artery branches gives off branches in the area of the medial pole and middle third of the adrenal gland and also in the area of the medial part of the renal surface. The size of the blood supply area - from 1.4 х 103 to 2.83 х 103 mm2. The rate of involvement into the blood supply - 22.96 %. The branches of the inferior suprarenal artery supply blood to the inferior surface of the adrenal gland, and some of these branches reach its lateral pole. The size of the blood supply area here is from 1.75 х 103 to 3.24 х 103 mm2, the rate of involvement into the blood supply is on the second position -26.53 %. The smallest area of blood supply of the adrenal gland is covered by the collateral suprarenal artery, which in 47 % of cases branches from the arcuate artery of the adipose capsule of the kidney (from 1,26 х 103 to 1,93 х 103 mm2). The rate of involvement -16.47 %.